Pizotifen inhibits the proliferation and invasion of gastric cancer cells - Jiang, Ying (Exp Ther Med, 2020)
Gastric cancer is the fifth most common malignancy and the third highest cause of cancer-associated mortality worldwide. Therefore, research on the pathogenesis of gastric cancer is of utmost importance. It has been reported that aberrant activation of the Wnt/β-catenin signaling pathway is involved in the occurrence and development of gastric cancer. In the present study, it was found that pizotifen could inhibit the viability of gastric cancer cell lines MNK45 and AGS cells in a dose-dependent manner. Pizotifen treatment suppressed cell migration and invasion in MNK45 and AGS cells, whilst also inducing apoptosis. Western blot analysis demonstrated that pizotifen blocked the expression of Wnt3a, β-catenin and N-cadherin, whilst increasing E-cadherin expression. In addition, BML-284, a pharmacological Wnt signaling activator, partially reversed the changes in the expression levels of β-catenin, N-cadherin and E-cadherin in MNK45 and AGS cells induced by pizotifen. Collectively, these findings suggested that pizotifen demonstrates potential as a novel anti-cancer drug for the treatment of gastric cancer by inhibiting the Wnt/β-catenin pathway.